IS LAPAROSCOPIC CHOLECYSTECTOMY A SAFE TREATMENT OPTION IN EMPYEMA OF GALL BLADDER? Laparoscopic Cholecystectomy - Afzal, Muhammad; Shahzad, Muhammad; Bajwa, Saleem Pervaiz; Ali, Amir Iqbal; Ali, Amir Iqbal; Usman, Rashid (Pakistan Armed Forces Medical Journal, 2015)
Original Article  Objective: To find out the effectiveness and safety of laparoscopic cholecystectomy for treatment of empyema gallbladder.Study Design: Quasi-experimental study.Place and duration of study: PNS Shifa Karachi and CMH Lahore, Pakistan from January 2010 to August 2013.Material and Methods: Out of 493 patients who underwent laparoscopic cholecystectomy (LC) by a single consultant surgeon during the study period, 40 patients who had empyema gall bladder on laparoscopic findings were included in the study. All patients with diagnosis of acute cholecystitis (n=117) who had no pus present in gall bladder and patients with diagnosis of biliary colic or chronic cholelithiasis (n=336) were excluded from the study.Results: Forty patients were diagnosed to have empyema gall bladder. LC was successfully completed in 39 patients (97.5%). In one patient (2.5%) the procedure was converted to open cholecystectomy (OC) due to finding of cholecystoduodenal fistula on laparoscopy. Mean operating time was up to 58.62 ± 26.33 minutes. Postoperative complications occurred in 3 (7.5%) of the operated patients. Mean duration of hospital stay was 1.7 ± 2.09 days. One patient with co-morbidity of diabetes mellitus died of septicemia resulting in a mortality rate of 2.5%.Conclusion: In laparoscopy for empyema gallbladder the complications are related to the advanced disease process and not to the approach. In skilled hands, laparoscopic cholecystectomy can be performed successfully in patients with diagnosis of empyema gallbladder.